Simultaneous integrated prophylactic cranial irradiation in sino-nasal cancer. (February 2017) - Jensen, Kenneth; Sharma, Maja Bendtsen; Lenler-Eriksen, Simon; Friis, Per; Holm, Anne Ivalu Sander
Abstract: Therapy for small cell cancer and high grade neuroendocrine tumours of the paranasal sinuses is extrapolated from the treatment of small cell lung cancer and paranasal cancer of different histologies. Prophylactic cranial irradiation has proven survival benefit in small cell lung cancer. Two patients with aggressive cancer of the paranasal sinuses received radiotherapy with simultaneous integrated prophylactic brain irradiation, using two sequential plans. Chemotherapy was given before, during and after radiotherapy. None of the patients had intracranial recurrence. One patient experienced severe, but transient encephalitis-like symptoms that could only be attributed to radiotherapy. No long term side effects in the CNS were observed. The treatment was feasible, but with possible severe, but transient side effects. It should be considered in cases with head and neck cancer, with a high risk of intracerebral metastasis, as well as a significant overlap between the primary irradiated volume and the brain.